DYNAMIC MEASUREMENTS OF THE NONLINEAR ELASTIC PARAMETER α IN ROCK UNDER VARYING CONDITIONS - Johnson P.A.; Zinszner B.; Rasolofosaon P.; Cohen-Tenoudji F.; Van Den Abeele K. (My University, 2004)
Since the exhaustive work by Adams and Coker at the Carnegie Institute in the early 1900s and the work of F. Birch's group at Harvard University conducted in the 1940s–1950s, it has been well documented that the quasi-static stress-strain behavior of rock is nonlinear and hysteretic. Over the past 20 years, there has been an increasing body of evidence suggesting that rocks are highly elastically nonlinear and hysteretic in their dynamic stress-strain response as well, even at extremely small strain amplitudes that are typical of laboratory measurements. In this work we present a compendium of measurements of the nonlinear elastic parameter α extracted from longitudinal (Young's mode) and flexural-mode resonance experiments in eight different rock types under a variety of saturation and thermal conditions. The nonlinear modulus α represents a measure of the dynamic hysteresis in the wave pressure-strain behavior. We believe that hysteresis is the primary cause of nonclassical nonlinear dynamics in rock, just as it is responsible for elastic nonlinear behavior in quasi-static observations. In dynamics, α is proportional to the wave speed and modulus reduction as a function of wave strain amplitude due to the hysteresis, based on our current model. The rocks tested include pure quartz sandstone (Fontainebleau), two sandstones that contain clay and other secondary mineralization (Berea and Meule), marble (Asian White), chalk, and three limestones (St. Pantaleon, Estaillades, and Lavoux). The values of α range from ∼500 to >100,000, depending on the rock type, damage, and/or water saturation state. Damaged samples exhibit significantly larger α than intact samples (hysteresis increases with damage quantity), and water saturation has an enormous influence on α from 0 to 15–30% water saturation.
Keywords: elastic nonlinearity; nonlinear acoustics; nonlinear elastic parameter α